Invasion potential and colonization dynamics of Fusarium proliferatum - Reyes Gaige, Andres Jose (Kansas State University, 2016)
The trade of food, plant, and animal products has increased the worldwide movement and establishment of exotic pathogens with dramatic negative impacts on plant systems. Fusarium proliferatum is a broad host-range pathogen and among the most common maize pathogens globally. It is often seed-borne and symptomless in maize, making it a high risk for introduction in maize and other grains. Considering the global distribution of maize and the wide host range and production of mycotoxins by F. proliferatum, a better understanding of its life history is needed. To provide markers for tracking F. proliferatum in laboratory experiments, strains of F. proliferatum were transformed to express a green fluorescent protein (GFP). Active dispersal (at least 1.5cm at 25°C and -50mb soil matric potential) and colonization of organic matter in nonsterile field soil was demonstrated in soil microcosms. Fusarium verticillioides is commonly isolated from maize seed also colonized by F. proliferatum. A red fluorescent (mRFP) F. verticillioides transformant was developed to study competition with F. proliferatum. For quantification in host tissues, a TaqMan multiplex qPCR protocol was developed using primer and probe sets targeting fragments of the green and red fluorescence genes to detect F. proliferatum and F. verticillioides, respectively. Prior colonization of maize tissues by F. verticillioides (p=0.6749) and other seed-borne microorganisms (p=0.1910) did not affect subsequent colonization by F. proliferatum. Genotyping-by-sequencing (GBS) was used to identify genetic markers in F. proliferatum. Primer sets based GBS markers were designed to allow detection of specific isolates in field experiments. F. proliferatum populations were characterized from maize seed prior to planting and again after harvest. End-point PCR identified F. proliferatum isolates containing the GBS marker. AFLP-fingerprinting indicated that 23 of the 817 F. proliferatum isolates contained the molecular marker and were genetically related to the original isolate. Based on the subclade and percentage similarity in UPGMA phylogenetic trees, and the population grouping observed in STRUCTURE and Principal Coordinate Analysis, these isolates could have a single origin and be clonal. Understanding the life cycle of F. proliferatum is critical for learning more about the risk of introducing seed-borne exotic isolates into new environments.
Keywords: Fusarium proliferatum; Life cycle; Invasion process; Active dispersal; Interspecific competition; Introduction and dissemination